DO CANCIONEIRO DAS DONAS ÀS CANTIGAS D’AMIGO DOS TROVADORES GALEGO-PORTUGUESES - Lemaire, Ria (2017)
During the time of the transition from the XIX to the XX century, the greatest Portuguese philologist was Carolina Michaëlis de Vasconcelos (1851-1925). When compiling and publishing Cancioneiro da Ajuda (1904), a medieval manuscript of male cantigas de amigo, or “songs” directed to a friend, she announces the “Cancioneiros das donas”, which would be dedicated to a Galician oral tradition, of female “authorship”, comprising musical works written and composed by women from the rural world, such as dance or work songs. However, the historical and scientific conditions of her time stopped her from completing the project, since, apart from accommodating these works under a masculine inscription, they made her part of a nation state project, which is reflected on historiography as erasure. This article follows this process, from Cancioneiro das Donas to Cantigas de amigo.